2017
DOI: 10.1093/hmg/ddx352
|View full text |Cite
|
Sign up to set email alerts
|

A novel SYN1 missense mutation in non-syndromic X-linked intellectual disability affects synaptic vesicle life cycle, clustering and mobility

Abstract: Intellectual Disability is a common and heterogeneous disorder characterized by limitations in intellectual functioning and adaptive behaviour, whose molecular mechanisms remain largely unknown. Among the numerous genes found to be involved in the pathogenesis of intellectual disability, 10% are located on the X-chromosome. We identified a missense mutation (c.236 C > G; p.S79W) in the SYN1 gene coding for synapsin I in the MRX50 family, affected by non-syndromic X-linked intellectual disability. Synapsin I is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 51 publications
1
45
0
Order By: Relevance
“…Therefore, we infer that different types of mutations cause different phenotypes, with truncating variants having an effect on firing/ bursting activity, as suggested by functional studies. 6,7 In conclusion, our update expands the phenotype of SYN1-related disorders, which represent a unique and recognizable condition. Epilepsy triggered by contact with water is a new and exciting area of research, and we encourage colleagues to test patients with this distinctive phenotype for SYN1 mutations, to clarify the hypotheses raised by our commentary.…”
Section: Hot Water Epilepsy and Syn1 Variantsmentioning
confidence: 72%
“…Therefore, we infer that different types of mutations cause different phenotypes, with truncating variants having an effect on firing/ bursting activity, as suggested by functional studies. 6,7 In conclusion, our update expands the phenotype of SYN1-related disorders, which represent a unique and recognizable condition. Epilepsy triggered by contact with water is a new and exciting area of research, and we encourage colleagues to test patients with this distinctive phenotype for SYN1 mutations, to clarify the hypotheses raised by our commentary.…”
Section: Hot Water Epilepsy and Syn1 Variantsmentioning
confidence: 72%
“…Previous studies reported that neuronal and synaptic loss in the cortex and hippocampus correlated best with cognitive dysfunction in AD, indicating that it is important in the pathogenesis [ 32 , 33 , 52 ]. The synapse-associated proteins, especially pre-synaptic Syn and post-synaptic PSD-95, play an important role in synaptic plasticity and memory formation [ 53 55 ]. It has been shown that pro-inflammatory cytokines are responsible for neuronal and synaptic loss, whereas anti-neuroinflammatory therapies may effectively attenuate synaptic damage and improve cognitive deficits [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Immunofluorescence experiments were performed as previously described 21 . Briefly, cells were rinsed once with phosphate buffer saline (PBS; Gibco #14200-056) for cells lines or Krebs-Ringer's solution (KRH)-EGTA (in mM: 130 NaCl, 5 KCl, 1.2 KH 2 PO 4 , 1.2 MgSO 4 , 2 MgCl 2 , 2 EGTA, 25 HEPES and 6 glucose, pH 7.4) for neurons.…”
Section: Cell Labelling Protocols and Image Acquisitionmentioning
confidence: 99%